Simple, Efficient Routing Schemes for All-Optical Networks - Flammini, Michele; Scheideler, Christian (SPAA)

A lower bound for randomized algebraic decision trees - Grigoriev, Dima; Karpinski, Marek; Meyer auf der Heide, Friedhelm; Smolensky, Roman (computational complexity)

Simulating Shared Memory in Real Time: On the Computation Power of Reconfigurable Architectures - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (Information and Computation)

Optimal Tradeoffs Between Size and Slowdown for Universal Parallel Networks - Meyer auf der Heide, Friedhelm; Storch, M.; Wanka, Rolf (Theory of Computing Systems)

Dynamic data structures for realtime management of large geometric scenes - Fischer, Matthias; Meyer auf der Heide, Friedhelm; Strothmann, Willy-Bernhard (5th Annual European Symposium on Algorithms (ESA '97))
We present a data structure problem which describes the requirements of a simple variant of fully dynamic walk-through animation: We assume the scene to consist of unit size balls in R2 or higher dimensions. The scene may be arbitrarily large and has to be stored in secondary memory (discs) with relatively slow access. We allow a visitor to walk in the scene, and a modeler to update the scene by insertions and deletions of balls. We focus on the realtime requirement of animation systems: For some t (specified by the computation power of (the rendering hardware of) the graphic workstation) the data structure has to guarantee that the balls within distance t of the current visitor's position are presented to the rendering hardware, 20 times per second. Insertions and deletions should also be available to the visitor with small delay, independent of the size of the scene. We present a data structure that fulfills the above task in realtime. Its runtime is output-sensitive, i.e. linear in a quantity close to the output size of the query. We further present (preliminary) experimental results indicating that our structure is efficient in practice.

Static and dynamic data management in networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold (Euro-Par'97 Parallel Processing)

Allocating weighted jobs in parallel - Berenbrink, Petra; Meyer auf der Heide, Friedhelm; Schröder, Klaus (Proceedings of the ninth annual ACM symposium on Parallel algorithms and architectures - SPAA '97)

Communication efficient parallel searching - Bäumker, Armin; Meyer auf der Heide, Friedhelm (Solving Irregularly Structured Problems in Parallel)

Routing on asyncronous processor networks - Karaivazoglou, Efstratios; Meyer auf der Heide, Friedhelm (Euro-Par'97 Parallel Processing)

Exploiting locality for data management in systems of limited bandwidth - Maggs, B.M.; Meyer auf der Heide, Friedhelm; Vöcking, Berthold; Westermann, Matthias (Proceedings 38th Annual Symposium on Foundations of Computer Science)

Parallel Computing in Paderborn: The SFB 376 “Massive Parallelism — Algorithms, Design Methods, Applications” - Meyer auf der Heide, Friedhelm; Decker, Thomas (Informatik ’97 Informatik als Innovationsmotor)

Routing on Networks of Optical Crossbars (Extended Abstract). - Schwarze, Frank; Meyer auf der Heide, Friedhelm; Schröder, Klaus (Euro-Par 1996)

Contention Resolution in Hashing Based Shared Memory Simulations - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker

A lower bound for randomized algebraic decision trees - Grigoriev, Dima; Karpinski, Marek; Meyer auf der Heide, Friedhelm; Smolensky, Roman (Proc. of 28th ACM-STOC)
We present a parallel algorithm for the rendering of complex three-dimensional scenes. The algorithm runs across heterogeneous architectures of PC-clusters consisting of a visualization-node, equipped with a powerful graphics adapter, and cluster nodes requiring weaker graphics capabilities only. The visualization-node renders a mixture of scene objects and simplified meshes (Reliefboards). The cluster nodes assist the visualization-node by asynchronous computing of Reliefboards, which are used to replace and render distant parts of the scene. Our algorithm is capable of gaining significant speedups if the cluster's nodes provide weak graphics adapters only. We trade the number of cluster nodes off the scene objects' image quality.

A Realistic Cost Model for the Communication Time in Parallel Programs - Fischer, Matthias; Rethmann, Jochen; Wachsmann, Alf (3rd Workshop on Abstract Machine Models for Parallel and Distributed Computing (AMW '96))
In this paper we develop a model for communication time on parallel computers consisting of processors and a service network, i.e., a network performing services like broadcast, synchronization, and global variables. The implementation of the service network is done on a free configurable Transputer network. Our cost model describes the communication time of accesses to global variables and consists of a multi-linear function. The cost model includes the parameters packet size, send hot spot, and the number of processors accessing global variables. These parameters influence the communication time in a high degree and capture important parameters like contention. We implement a Bitonic Sort and a Connected Components algorithm (among others) and we show that our model is able to predict the communication time within a 10% error if indirect service networks are used. The applications show that it is easy for a programmer to determine the parameter values for our model and that our new cost model precisely predicts the communication time of parallel algorithms. Furthermore, we minimize the communication time of accesses to global variables by finding a balance between the number of messages in the network and their size. Our model predicts the optimal values for these parameters which we validate by experiments. A modified implementation of our routing which determines on-line the optimal parameter values for an access to a global variable achieves good speed ups.

Realistic parallel algorithms: Priority queue operations and selection for the BSP* Model - Bäumker, Armin; Dittrich, Wolfgang; Meyer auf der Heide, Friedhelm; Rieping, Ingo (Lecture Notes in Computer Science)

A Realistic Cost Model for the Communication Time in Parallel Programs on Parallel Computers Using a Service Hardware - Fischer, Matthias; Rethmann, Jochen; Wachsmann, Alf
In this report, we develop a cost model for the communication time on parallel computers consisting of processors and a service network, i.e., a network performing services like broadcast, synchronization, and global variables. Because we do not have a parallel computer at our disposal that is equipped with a service network, we emulate the service network on a reconfigurable Transputer network. Our cost model describes the communication time of accesses to global variables and consists of a multilinear function. The cost model includes the parameters packet size, send hot spot (the number of messages sent out by one processor), and number of processors accessing global variables. We show that these parameters influence the communication time in a high degree and capture important parameters like network contention. We implement a Bitonic Sort, Sample Sort, Matrix Multiplication, and Connected Components algorithm, and we show that our model is able to predict the communication time within a 10% error if indirect service networks are used. The applications show that it is easy for a programer to determine the parameter values for our model and that our new cost model precisely predicts the communication time of parallel algorithms. We explore the interaction of hot spots and asynchrony and show that the influence of hot spots to the communication time is not as high as one would expect from theoretical considerations in a synchronous model. Therefore, we do not apprehend the hot spot in our cost model. Furthermore, we minimize the communication time of accesses to global variables by finding a balance between the number of messages in the network and their size. Our model predicts the optimal values for these parameters which we validate by experiments. A modified implementation of our routing which determines online the optimal parameter values for an access to a global variable achieves good speed ups.

Universal routing strategies - Scheideler, Christian

Exploiting Storage Redundancy to Speed up Randomized Shared Memory Simulations - Meyer auf der Heide, Friedhelm; Scheideler, Christian; Stemann, Volker (Theor. Comput. Sci.)

Deterministic Routing with Bounded Buffers: Turning Offline into Online Protocols - Meyer auf der Heide, Friedhelm; Scheideler, Christian (FOCS)